Identifying Employee Job Satisfaction Level on Pulslitbang Tekmira - Permatasari, Erlina; Tjakraatmadja, Jann Hidajat (Journal of Business and Management, 2014)
Pusat Penelitian dan Pengembangan Teknologi Mineral dan Batubara or better known as puslitbang tekMIRA is the government institution under the ministry of energy and mineral resources, which primarily textual although some basic tasks and functions through research and developmental activities in the field of mineral and coal. In 2014, they have 275 employees. The main research is to know the level of employee job satisfaction in the puslitbang tekMIRA. It focuses on the five facets based on Herzberg two factor theory and hierarchy of Maslow and measured by Job Descriptive Index questionnaire. The variables that be measure are, work it self, pay, promotion opportunity, supervision, and co-worker. The research used descriptive statistic and SPSS 19 to analyzed data. The result of this research shows that the level satisfaction of employee in the main office of puslitbang tekMIRA is satisfied, but still needed to be improving.Keywords: employee job satisfaction, job descriptive index